PENERAPAN KONSEP SMART CITY PADA KONTEKS KABUPATEN (KONSEP SMART CITY PADA KABUPATEN KULON PROGO) - Nday, Samuel Umbu; Djunaedi, Achmad (REKSABUMI, 2022)
The Application of smart cities to regency area has not been widely implemented or is a newplanning application. Concept that implemented to region of indonesia will give different result andeffect specifically to regency area that have different characteristic from another region. Variouschange that caused from the start of application in 2018 until present brought impact to society,regional and government. Case study of the application of smart city concept is process will lookdirectly at practice of smart city development with execution of the programs. The used method in theresearch is interview, observation, and data collection. The result will relate to the stage and processof growth, influence of factor, and the finding of changes that important in the development or willrelates to progress of direction and focus of implementation throughout the practice of smart cityprograms. Factors that important cannot be separated from the growth of smart city development.Various change will be happened to Kulon Progo Regency as one of the regions that encouragesapplication of smart city to brought benefit widely for government and society. The representation ofthe result is findings of revelation to the goal and the existing of development.